2020
DOI: 10.1007/s00198-020-05341-z
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a national hip fracture registry to evaluate the profile of patients in whom antiosteoporotic treatment is prescribed following hospital discharge

Abstract: This study was carried out to describe the profile of prescription of antiosteoporotic treatment at discharge after a hip fracture in the Spanish National Hip Fracture Registry. Prescription rates among hospitals ranged from 0 to 94% of patients discharged. The prescription rate was higher among patients with better cognitive and functional baseline status. Purpose National hip fracture registries are useful for assessing current care processes. The goals of this study were as follows: first, to know the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Regarding initiation of osteoporosis therapy, higher frequency was observed in level I trauma centers. These findings match with an evaluation of the Spanish Hip Fracture Registry by Alarcon et al, where anti-osteoporotic therapy was prescribed significantly more often at high-volume hospitals [ 24 ]. Furthermore, Kristensen et al found that interventions to prevent future falls were taken more frequently at high-volume hospitals [ 18 ].…”
Section: Discussionsupporting
confidence: 88%
“…Regarding initiation of osteoporosis therapy, higher frequency was observed in level I trauma centers. These findings match with an evaluation of the Spanish Hip Fracture Registry by Alarcon et al, where anti-osteoporotic therapy was prescribed significantly more often at high-volume hospitals [ 24 ]. Furthermore, Kristensen et al found that interventions to prevent future falls were taken more frequently at high-volume hospitals [ 18 ].…”
Section: Discussionsupporting
confidence: 88%
“…Benchmarking of care for secondary prevention of fragility fractures is a component of the IOF Capture the Fracture® program [40], and of national fracture liaison service standards based on the 5IQ model [7][8][9]. Hip fracture registries, that have been established in several countries, also enable benchmarking of acute perioperative care and secondary fracture prevention after hip fracture [41][42][43][44][45][46].…”
Section: Benchmarking and Audit Activitiesmentioning
confidence: 99%